Why 159°?: a story about the dropping of the Hiroshima atom bomb. (3rd March 2015) - Prunty, Sean L
Abstract: This paper presents an analysis of the evasive manoeuvre undertaken by the pilot of the Enola Gay aircraft following the dropping of the first uranium bomb. The pilot was instructed to make a 159° turn following the bomb's release in order to acquire the greatest distance from the point at which the bomb explodes. Accordingly, the objective here is to investigate why the angle should be exactly 159°. The optimum flight-path to maximize the distance from the detonation point is analysed by considering the escape or exit angle taken by the aircraft following a turning-manoeuvre that points it directly away from the detonation site. A range of escape angles are predicted based on the requirement to exit the turning radius prior to detonation. By using information that appeared in a historical account of the event regarding the manoeuvre undertaken by the pilot following the release of the bomb, an estimate is made of the escape angle. Despite the fact that the result shows reasonable agreement with the value of 159°, some uncertainty is expressed as to the close coincidence obtained. In addition, the location of the aircraft and the time of arrival of the shock wave following detonation are also briefly discussed.